Initial letters on the pages of Ukrainian old printed books of the 17th-18th centuries - Yukhymets H. M.; Tsynkovska I. I. (Рукописна та книжкова спадщина України, 2017)

(untitled)
The article is devoted to such a complicated and little studied element of artistic decoration of Ukrainian printed books of the 17th-18th centuries as capital letters. The authors research old printed books from the collection of imprints of the Kyiv-Pechersk Lavra’s typography. Various topics, iconography, compositional and artistic stylistic features of miniature illustrations of initial letters, their location on book pages, content correspondence or discrepancy with a text, usage of one clichй in various editions provide multiple new possibilities to researchers. Especially the authors accentuate iconography of gospel and life subjects, as well as the source studies analysis of initial letters, which in Ukrainian old printed editions of Baroque epoch impress with innovation of subject development and the ambition for original decisions of complex compositional tasks conditioned not only by the size and format of an initial, but also by the form and location of the letter itself in a certain decorative space.